Sometimes collaboration is the better strategy : institutional context and the calculative and collaborative HRM-performance relationship in the Nordics, 1999–2021 - Einarsdottir, Arney; Bévort, Frans; Sandvik, Alexander Madsen; Rizov, Marian; Smale, Adam; Tengblad, Stefan (Taylor & Francis, 2025)
This study challenges widespread universalist, or best practice, assumptions about HRM. To do this, we analyze the relationship between collaborative and calculative HRM and organizational performance, comparing Nordic CME countries to other institutional contexts and testing for the effect of time on the relationship. We first replicate a study by Rizov and Croucher (Citation2009), showing that collaborative HRM has a stronger relation to performance, using the 1999 European Cranet survey. The result remains the same in 2021. We find that the Nordic context positively moderates the collaborative HRM performance relationship. The study is then extended by examining the same relationships for 1999 and 2021 in a more contrasting and theory-guided sample including five Nordic-CME countries and five liberal market economies (LMEs) from four continents. Results confirm that collaborative HRM practices are still more important for organizational performance than calculative practices. Furthermore, the Nordic institutional CME context moderates the relationships between collaborative HRM practices and organizational performance in 1999 and 2021 in both the European and the Nordic-LME samples. Finally, we found no change in the effects of collaborative and calculative HRM practices on performance 22 years later. The study contributes to institutional theory and to comparative and international HRM.
Keywords: Strategic HRM; calculative HRM; collaborative HRM; organizational performance; institutional theory; Nordic model; fi=Henkilöstöjohtaminen|en=Human Resource Management|